Mekanisme dan Faktor Kimia yang Mendasari Resistensi Beberapa Varietas Padi Terhadap Wereng Batang Coklat Nilaparvata Lugens Stal (Homoptera: Delphacidae) - Syafrida Manuwoto; Hendra Adijuwana (Jurnal Ilmu Pertanian Indonesia, 1991)
The brown planthopper (BPH) Nilparvata lugens Stal (Homoptera: Delphacidae) is one of the most important rice pest in Indonesia. Integrated pest management (IPM) is the only way of controlling the BPH. The use of resistant varieties is an important component of IPM. The development of BPH biotypes and agricultural practises cause the resistant varieties become susceptible in only 4-6 growing seasons. Understanding BPH - rice plant interactions are necesary. This greenhouse and laboratory studies were to unravel the mechanism and plant chemicals that might play a role in rice plant resistance of selected rice varieties: Cisadane, IR36, IR48, IR64, IR56, Kelara, and Bahbutong. Pelita I-I was used as susceptible check. The BPH colony originating from catches in 1986 in Yogyakarta was used in this study. Various experiments were carried out: evaluation of plant damage, the preference of BPH for feeding and ovaiposition, and population development study. The plants contens of protein, amino acids, water, potassium, calcium, and silica were measured. The mechanism of plant resistance to BPH on IR36, IR48, IR56, IR64, Kelara, and Bahbutong were identified as non-preference and antibiosis. The antibiosis mechanism was more prominent in IR48 and Bahbutong. The plant content of protein, potassium, calcium, and silica may take part in the basis of resistance mechanism. Further studies will be carried out.